The Portraits of Women's Dual Roles in Two Japanese Novels - Risman, Yunita El (J-Litera: Jurnal Kajian Bahasa, Sastra dan Budaya Jepang, 2023)
This study aims to show the portrait of women's dual roles in two Japanese novels, Out by Natsuo Kirino and Absolute Justice by Akiyoshi Rikako. This research stems from the author's interest in seeing the comparison and similarity of the portrait of women's dual roles reflected in the two Japan's novel. This research uses the method of comparative literature, which focuses on how the authors of the two novels present female characters, namely the character Yayoi and the character Yumiko, who play a dual role as a wife and housewife and also as a woman who has a professional career outside the home, as well as how the goals the author wants to achieve are depicted in the characters Yayoi and Yumiko. The results show that the dual roles of Out is more dominant than that of Absolute Justice, while the goals of the two novels are also different. The novel Out is oriented toward "Working Life." While the novel Absolute Justice is more dominantly oriented towards "Family and Childcare.”